1970
DOI: 10.1037/h0028581
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of the role of the hypothalamus in motivation.

Abstract: The view that stimulation of discrete hypothalamic areas elicits specific drive states is challenged by recent evidence. Data are presented to support the view that there is much less anatomical specificity within the hypothalamus than is commonly assumed. Significant differences between natural states of hunger and thirst and those associated with the elicitation of eating and drinking are described. Additional information related to species differences, the role of prior experience, and an analysis of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
126
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(129 citation statements)
references
References 35 publications
3
126
0
Order By: Relevance
“…Brain stimulation electrodes are vigorously selfstimulated by rats in structures such as lateral hypothalamus, septum, accumbens, or the medial forebrain bundle (Olds and Milner 1954;Shizgal et al 2001) and often simultaneously motivate animals to eat, drink, engage in sex, etc. (Hoebel 1988;Valenstein et al 1970). However, the same electrodes that make rats 'want' to eat food more voraciously still fail to make rats 'like' food more hedonically (Berridge and Valenstein 1991).…”
Section: Dopamine-beyond Learning Too?mentioning
confidence: 99%
“…Brain stimulation electrodes are vigorously selfstimulated by rats in structures such as lateral hypothalamus, septum, accumbens, or the medial forebrain bundle (Olds and Milner 1954;Shizgal et al 2001) and often simultaneously motivate animals to eat, drink, engage in sex, etc. (Hoebel 1988;Valenstein et al 1970). However, the same electrodes that make rats 'want' to eat food more voraciously still fail to make rats 'like' food more hedonically (Berridge and Valenstein 1991).…”
Section: Dopamine-beyond Learning Too?mentioning
confidence: 99%
“…The Hy provides the primary brain control over the endocrine system through interactions with the pituitary. It plays a major role in the regulation of motivated behavior and homeostatic processes (Sewards and Sewards, 2003;Valenstein et al, 1970), regulates the release of cortisol and other hormones into the bloodstream with diverse effects (Tsigos and Chrousos, 2002), and interacts with the autonomic nervous system through large reciprocal connections with the PAG and other brainstem nuclei (Saper et al, 1976). Based on these and many other findings, the Hy plays a central role in brain responses to threat and stress and regulation of the body.…”
Section: The Present Approach: Methodological Overview and Neuroscienmentioning
confidence: 99%
“…While the within-subject comparisons of the present study preclude this possibility, another possibility exists. Valenstein, Cox, and Kakolewski (1970) found that rather long (10 sec or more) trains of hypothalamic stimulation decreased normal deprivation-elicited food and water consumption following stimulation. It is possible that this post-ESB inhibition of drinking occurred in the present experiments, and precluded licking under ESB schedules.…”
Section: Methodsmentioning
confidence: 99%